Oral Nifedipine Versus Intravenous Labetalol in the Management of Severe Pregnancy Induced Hypertension: A Randomized Control Trial (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Pregnancy-also known as gestation is the time during which one or more offspring develops inside a woman. A multiple pregnancy involves more than one offspring, such as with twins. Pregnancy usually occurs by sexual intercourse, but can occur through assisted reproductive technology protedures. To assess the efficacy of oral Nifedipine and I/V Labetalol for lowering BP in severe PIH after 28 weeks of pregnancy.Materials and methods: In this study 100 subjects were selected with severe pregnancy induced hypertension as per inclusion criteria. After taking informed written consent they were randomly allocated into two groups, A & B. Group A received initially tablet nifedipine 10 mg orally with repeated doses of 20 mg every 20 minutes upto five doses while Group B received intravenous labetalol 20 mg initially followed by escalating doses of 40, 80, 80 and 80 mg every 20 minutes until the therapeutic goal blood pressure Systolic £ 150 mmHg & diastolic £ 100 mmHg was achieved. Primary outcomes were the time interval and the number of doses needed to achieve a blood pressure of £ 150/100 mmHg, Secondary outcomes were fetomaternal safety, efficacy and side effects of both drugs. The outcomes were recorded in a preformed data collection sheet. All the data were analyzed by computer based software SPSS version 19 (SPSS Inc, Chicago, IL, USA). P